Green Entrepreneurship in Islamic Perspective: Building Sustainable Innovation Based on Ethical and Environmental Values - Andreas Tigor Oktaga; Ahmad Dwi Nurdiyanto; Gulrukh Tukhlieva (International Forum of Researchers and Lecturers, 2024)
This research explores the integration of Islamic values into sustainable entrepreneurship, focusing on Muslim entrepreneurs who incorporate green innovation practices in their businesses. Despite growing awareness of sustainability, many Muslim entrepreneurs face challenges in aligning Islamic ethical principles with modern green business practices. This study aims to identify key Islamic values that guide sustainable entrepreneurship and analyze how faith-based motivations foster a culture of eco-conscious innovation. A qualitative descriptive research design, using a phenomenological approach, was employed to explore the experiences of Muslim entrepreneurs in environmentally sustainable sectors, including organic farming, renewable energy, and eco-friendly product manufacturing. Data was collected through semi-structured interviews, and thematic analysis was used to identify patterns of Islamic ethical influence on decision-making and innovation practices. The study found that Islamic entrepreneurship is rooted in values such as justice, stewardship, and social responsibility, which guide environmentally responsible innovation. These values encourage long-term sustainability, with a focus on community welfare and ecological preservation. The study also identified that Muslim entrepreneurs face barriers such as limited access to Sharia-compliant financing and financial literacy. The conclusions suggest promoting Sharia-based sustainable business frameworks, developing Islamic green financing instruments, and incorporating environmental education within Islamic entrepreneurship programs to foster more eco-conscious innovations. These findings offer valuable insights for policymakers, financial institutions, and entrepreneurs looking to integrate Islamic principles with sustainable development.